INNOVATIVE TEACHING IN MILLENNIAL ERA - Ali, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This artcle describes about the changes of students behavior in millennial era and the chalanges faced by the teachers. The teachers should conduct an innovative in teaching and learning.  Focus of the discussion is innovation and the process of doing an innovative teaching in millennial era. The aims is to find the process and model of innovative teaching in millennial era. This studi uses the contant analysis method . This article concludes that the activities for doing innovation in teaching learning process should understand character of students and follow the  procedure and use a model that produce profit academically and non-academic in millennial era.